Healthcare Workers’ Knowledge, Perception, and Willingness to Accept HPV Vaccination for Their Children: Implications for Advocacy - Anenga, Ushakuma Michael; Ajunwa, Matthew Ogiri; Okpe, Samuel Okoh; Elebe, Isaac Egba; Anenga, Rachael Nguveren; Tatabe, Yakaka Mustapha; Nkemdeme, Juliet Adamezie; Ilikannu, Samuel Okwuchukwu (Asian Pacific Journal of Cancer Nursing, 2026)
Background: Human papillomavirus (HPV) vaccination is a key strategy for preventing cervical cancer and other HPV-related malignancies. With the recent introduction of HPV vaccine into Nigeria’s routine immunization programme, healthcare workers play a critical role in influencing uptake through advocacy and recommendation. This study assessed healthcare workers’ knowledge, perception, and willingness to vaccinate their children against HPV, and examined predictors of vaccine advocacy. Methods: A descriptive cross-sectional analytical study was conducted among 255 healthcare workers at Benue State University Teaching Hospital, Makurdi, Nigeria, between April 2025 and February 2026. Data were collected using a structured self-administered questionnaire assessing sociodemographic characteristics, knowledge (HPV-KQ), perception (adapted HPV Attitudes and Beliefs Scale), willingness to vaccinate one’s child, and advocacy practices. Descriptive statistics, chi-square tests, and multivariable logistic regression were performed using SPSS version 27. Statistical significance was set at p < 0.05. Results: The mean age of respondents was 36.4 ± 9.9 years, and 69.0% were female. Good knowledge of HPV and vaccination was observed in 78.0% of participants, while 87.1% demonstrated positive perception. Overall, 82.7% were willing to vaccinate their child against HPV, and 55.3% reported routine engagement in vaccination advocacy. Perception was strongly associated with willingness (χ² = 30.411, p < 0.001). After adjustment, positive perception remained the only independent predictor of willingness (AOR = 6.12, 95% CI: 2.54–14.71, p < 0.001). Willingness to vaccinate one’s child independently predicted engagement in advocacy (AOR = 3.32, 95% CI: 1.59–6.92, p = 0.001). Knowledge was not independently associated with willingness or advocacy. Conclusion: Although healthcare workers demonstrated good knowledge and high willingness to accept HPV vaccination for their children, perception emerged as the strongest determinant of vaccine acceptance and advocacy. Interventions aimed at strengthening healthcare workers’ confidence and attitudes toward HPV vaccination may enhance advocacy efforts and improve vaccine uptake in Nigeria.